PENGARUH PENCAMPURAN LAPISAN OLAH DAN LAPISAN TAPAK BAJAK TERHADAP KARAKTERISTIK SIFAT KIMIA TANAH SAWAH - Rafdea Syafitri; H Hermansah; Y Yulnafatmawita (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The increasing of Indonesian population has led to a decrease in the area of rice fields in Indonesia. Therefore, it is needed to increase the fertility and the productivity of paddy soil. Since 1984, several attempts have been made to increase the productivity of paddy soils through the green revolution program, but this has had a negative effect on the fertility of paddy soils. The exploitation of paddy soil layers which has been increasing for years has decreased paddy soil. Other aspects of paddy soil management need to be done; one of them is a mixture of top soil layer with plow pan layer. The mixture of top soil layer with the plow pan layer is expected to improve the soil fertility. This research was conducted with the aim to study the effect of the top soil layer and plow pan layer on the chemical properties of paddy soil. This study used a completely randomized design with five treatments of mixing paddy soil layers and three replications. The treatments were A1 = 100% top soil layer, A2 = 75% top soil layer + 25% plow pan layer, A3 = 50% top soil layer + 50% plow pan layer, A4 = 25% top soil layer + 75% plow pan layer, and A5 = 100% plow pan layer. The results showed that the A2 treatment gave changes in optimal soil chemical properties. The A2 treatment decreased EH value to 133 mV, increased pH to 6.08, organic-C 2.22%, total N 0.30%, available P 27.94%, CEC 38.50%, exchangeable Ca 0.88 me 100g-1, exchangeable Mg 0.37%, exchangeable K 0.94% and exchangeable Nadd 0.17%.